The Pattern of Sharia Economic Thought: A Viewpoint Against the Quran - Putra, Haris Maiza; Farid, Diana (STAI AL-FALAH CICALENGKA, 2021)
The economy that is developing in the current era leads to the western economy, not many know that in its history Islamic economics has triumphed in its time. The main problem is the dishonesty of western economists when mentioning scientific references. This does not mean that there is no historical basis for Islamic economics. The purpose of this study is to determine the style and methodology of Islamic economic thought. This research is a descriptive qualitative research. This research is a library research. The results of the study show that economic discourse in the Islamic perspective is very much found in the classical Islamic literature. The pattern of Islamic economic thought includes textual, substantialist, and liberal thinking. Islamic scientists have studied various economic dimensions in Islamic civilization at that time such as the problem of prices, market mechanisms, demand, supply, poverty, economic growth, inflation, money demand and supply, zakat, taxes, state revenues and expenditures and others. However, there is no specific scientific discipline that discusses various economic phenomena and activities. Keywords: Sharia Economics, History, Methodology, Patterns of Thought. Abstrak Ekonomi yang berkembang era sekarang ini bermuara pada ekonomi barat, tidak banyak yang mengetahui bahwa dalam sejarahnya ekonomi Islam pernah berjaya pada masanya. Masalah utamanya adalah tidak jujurnya ekonom barat ketika menyebutkan rujukan keilmuannya. Bukan berarti bahwa tidak ada landasan historis keilmuan ekonomi Islam. Tujuan dari penelitian ini adalah untuk mengetahui corak dan metodologi pemikiran ekonomi syari’ah. Penelitian ini termasuk jenis penelitian kualitatif deskriptif, penelitian ini adalah penelitian kepustakaan. Hasil penelitian menunjukkan bahwa diskursus ekonomi dalam perspektif Islam sangat banyak ditemukan dalam khazanah literatur klasik Islam. Corak pemikiran ekonomi syariah meliputi pemikiran tekstualis, substansialis, dan liberalis. Para ilmuwan Islam sudah mengkaji berbagai dimensi-dimensi ekonomi dalam peradaban Islam waktu itu seperti masalah harga, mekanisme pasar, permintaan, penawaran, kemiskinan, pertumbuhan ekonomi, inflasi, money demand and supply, zakat, pajak, penerimaan dan pengeluaran negara dan lain-lain. Namun demikian, belum ada disiplin ilmu khusus yang membahas berbagai fenomena dan aktivitas ekonomi. Kata Kunci: Ekonomi Syari’ah, Sejarah, Metodologi, Corak Pemikiran.